Transforming Mathematical Model into Agent-Oriented Model and Simulation Through Requirement Engineering: A Preliminary Result - Loh, Gary Chee Wyai; Cheah, Wai Shiang; Nissom, Shane (2018)
Many of the mathematical models developed in the past have served as a vast repository of knowledge that is rigid and difficult to repurpose and transfer to different stakeholders or modelling technique due to the high learning curves. Even if a mathematical model can be understood, converting the understanding of the mathematical model into agent based modelling and simulation (ABMS) is not straightforward as it is difficult to describe clearly and succinctly due to more data are required and significant software engineering expertise is needed to develop ABMS. We adopt requirement engineering technique to bridge the gap across the modelling techniques. The requirement engineering technique is used to understand the mathematical model and turn into agent context for agent modelling and simulation. This paper presents the preliminary result in adopting the proposed requirement engineering techniques for model transformation.From the results, the agent oriented requirement engineering known as eHOMER is able to transform the mathematical model into ABMS.Hence, the agent modeller can reuse the mathematical model without reinventing the wheel.